An elevational trend of body size variation in a cold-climate agamid lizard, Phrynocephalus theobaldi. Issue 3 (1st June 2015) - Jin, Yuanting; Liao, Pinghu
Abstract: The pattern that many ectotherms have smaller body sizes in cold environments follows the converse to Bergmann's rule and is most frequently found in lizards. Allen's rule predicts animals from warm climates usually have longer tails and limbs, while these traits tend to be shorter in individuals from cold climates. We examined body size variation in an endemic Chinese lizard Phrynocephalus theobaldi along a broad elevational gradient (3, 600–5, 000 m on the Qinghai-Tibetan Plateau). Female body size showed a U-shaped cline, decreasing with increased elevation within the range 3, 600–4, 200 m, but increasing at elevations > 4200 m. Male body size continued to increase with increasing elevations. Both sexes showed an increased pattern of extremity length with elevation that does not conform to Allen's rule. Limb length and tail length increased along the elevational gradients. In terms of color pattern, an abdominal black speckled area appears at elevations >4, 200 m. This trait increases in size with increased elevation. Unlike most studies, our results indicated that annual sunshine hours corresponding to the activity period of the lizards could play an important role on the positive body size cline in environments at very high elevations > 4200 m.